A dosimetric comparison between ICRP and ORNL phantoms from exposure to 137Cs contaminated soil. (June 2023) - Živković, Milena; Shahmohammadi Beni, Mehrdad; Yu, Peter K.N.; Watabe, Hiroshi; Krstić, Dragana; Nikezić, Dragoslav
Abstract: The 137 Cs soil contamination has detrimental effects on human health. The penetration and distribution of 137 Cs radionuclides at different soil depths were investigated. Two sampling campaigns in 2001 and 2018 were performed to determine the 137 Cs activity in soil at 11 locations around the city of Kragujevac in central Serbia. The ICRP and ORNL humanoid phantom models were used to determine equivalent and effective doses from the experimentally measured data, and conversion coefficients were obtained from Monte Carlo computations. The results show a general decrease in 137 Cs concentration in samples that were taken in 2018. However, variation of 137 Cs concentration was observed at different locations that did not match the expected reduction of 137 Cs concentration based on its half-life. Considering the computational results, no significant difference between the estimated equivalent dose rate per unit activity of 137 Cs (conversion coefficients) between ICRP and ORNL phantoms was observed. In addition, two open-source computer programs for PC and Android devices were developed for users to determine the equivalent and effective doses for their specific cases; this gives the users an easy-to-use interface and portable tools to determine dosimetric quantities. The obtained results and the developed tools would be useful for future investigations related to soil contamination by 137 Cs radionuclides that require extensive future studies. Highlights: Cs-137 in soil measured in two campaign. Cs-137 in soil vertical distribution. Effective dose from Cs-137 in soil as the source of external irradiation. Comparison between ORNL and voxel humanoid phantoms.